ALTERATION OF EXPERIMENTAL POLIOMYELITIS INFECTION IN THE SYRIAN HAMSTER WITH THE AID OF CORTISONE - Shwartzman, Gregory (The Rockefeller University Press, 1952)
Cortisone produces a significant enhancement of infection with MEF1 and Lansing strains of poliomyelitis virus in the Syrian hamster. The enhancement manifests itself in increased severity of symptoms, shortening of the incubation period, marked reduction in survival time and a high mortality rate. The effect of cortisone is protracted, the duration depending on the dose used. There is a reciprocal relationship between the dose of cortisone and the amount of virus, the larger the dose of the hormone, the smaller the amount of virus being necessary to produce the infection. An amount of virus of low infectivity causes amarked disease with a high mortality rate in hamsters receiving a single injection of 3 mg. of cortisone, while a dose as small as 2 mg. gives a highly fatal disease with a stronger concentration of the virus. There is a 2 log increase in the concentration of the virus in cortisone-treated hamsters. Hamsters from various sources seem to respond differently to the enhancing effect of cortisone, one breed showing no enhancement of the infection with the Lansing strain. Hormones other than cortisone, i.e., DCA, progesterone, diethylstilbestrol, and fast and slow acting ACTH injected repeatedly fail to modify the poliomyelitis infection in the hamster.